Do Dipteryx alata Vogel seedlings recover the quality and the photosynthetic and antioxidant responses in the post-flooding? - Linné, J. A.; Jesus, M. V.; Lima, V. T. [UNESP]; Reis, L. C.; Santos, C. C.; Scalon, S. P.Q.; Dresch, D. M. (FapUNIFESP (SciELO), 2021)
Dipteryx alata Vogel is a tree species widely found in Cerrado, settling preferentially in well drained soils. Studies related to ecophysiology of D. alata may contribute to the decision making about using seedlings of this species in projects aimed at the recovery of degraded areas where seasonal flooding happens. This study aimed to assess the effects of flooding on photosynthetic and antioxidant metabolism and quality of D. alata seedlings cultivated or not under flooding during four assessment periods (0, 20, 40, and 60 days), followed by 100 days after the end of each assessment period (0+100, 20+100, 40+100, and 60+100 days), allowing verifying the potential for post-flooding recovery. Flooded plants showed lower photosynthetic efficiency than non-flooded plants, regardless of the periods of exposure. However, this efficiency was recovered in the post-flooding, with values similar to that of the non-flooded seedlings. Moreover, the damage to FV/FM was evidenced by an increase in the period of exposure to flooding, but recovery was also observed at this stage of the photosynthetic metabolism. Seedling quality decreased under flooding, not varying between periods of exposure, but remained lower although the increase observed in the post-flooding period, with no recovery after flooding. The occurrence of hypertrophied lenticels associated with physiological changes and an efficient antioxidant enzyme system might have contributed to the survival and recovery of these seedlings. Thus, this species is sensitive to flooding stress but capable of adjusting and recovering metabolic characteristics at 100 days after the suspension of the water stress, but with no recovery in seedling quality. Thus, we suggested plasticity under the cultivation condition and determined that the time of 100 days is not enough for the complete resumption of growth.